Solar Thermoelectric Technologies for Power Generation - Li, Guiqiang; Ma, Xiaoli; Shittu, Samson; Zhao, Xudong (Springer (part of Springer Nature), 2025)
© 2019, Springer Nature Switzerland AG. Thermoelectric power generation (TEG) is the most effective process that can create electrical current from a thermal gradient directly, based on the Seebeck effect. Solar energy as renewable energy can provide the thermal energy to produce the temperature difference between the hot and cold sides of the thermoelectric device. This chapter introduces various solar thermoelectric technologies including micro-channel heat pipe evacuated tube solar collector incorporated thermoelectric power generation system, solar concentrating thermoelectric generator using the micro-channel heat pipe array, and novel photovoltaic–thermoelectric power generation system. The details of these systems are illustrated, and their performance is analyzed. This chapter would provide a valuable reference for the study and applications of the solar thermoelectric power generation technologies.